An eigenvalue problem for the differential operator with an integral condition - Jakubėlienė, Kristina (Lietuvos matematikos rinkinys, 2012)
We analyze solution of a two-dimensional parabolic equation with a nonlocal integral condition by a locally one-dimensional method. The main aim of the paper is to deduce stability conditions of a system of one-dimensional equations with one integral condition. To this end, we analyze the structure of the spectrum of the differential operator with an integral condition.